Taxation, Reranking and Equivalence Scales - Justin van de Ven; John Creedy (New Zealand Government, The Treasury, 2003)
This paper considers whether an equivalence scale implicit in transfer policy can be inferred from summary measures of reranking (whereby the rank order of pre-tax incomes is different from that of the post-tax distribution). It is conjectured that, if the government has a distributional objective and formulates tax policy with a view to equitable treatment of income units, then adopting the scale that is implicit in government transfer policy should identify only the reranking that has no equity foundation. This motivates the question: Is the incidence of reranking associated with a transfer system minimised by the equivalence scale that is implicit in the transfer system? The analysis presented in this paper suggests that the equivalence scale which minimises reranking, while not necessarily equal to the closest approximation to the one that is implicit in transfer policy, is nevertheless in its vicinity.
Keywords: D63; 330; Adult equivalence scales; reranking; horizontal equity